1992
DOI: 10.1177/155005949202300103
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Rhythm Power and the Effect of Photic Stimulation in Migraine with Brain Mapping

Abstract: The topographic maps of 50 patients suffering from migraine with or without aura were compared to the brain maps of 20 normal controls and 20 patients with tension-type headaches. Only the migraine group showed a significant decrement of alpha rhythm power, during rest with eyes closed, at the posterior areas of the brain, and a significant increment of alpha power at the same regions during IPS at 20 c/sec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…More specifically in migraine, increased alpha power has been recorded in posterior brain regions, while activity in the frontal lobe has revealed decreased activity in alpha generators (Clemens et al, 2008; Cao et al, 2018). Other studies have also reported on a global inter-ictal decrease of EEG activity (Tsounis and Varfis, 1992; Cao et al, 2016) and on an association between slower alpha activity and greater disease and attack durations (Bjørk et al, 2009). Whereas in FM, decreased alpha, increased beta (Vanneste et al, 2017) and augmented theta activity (Fallon et al, 2018) have been found in different cortical areas and have also been reported to positively correlate with clinical symptoms.…”
Section: Abnormal Eeg Responses As a Shared Mechanism For Smd And Painmentioning
confidence: 91%
“…More specifically in migraine, increased alpha power has been recorded in posterior brain regions, while activity in the frontal lobe has revealed decreased activity in alpha generators (Clemens et al, 2008; Cao et al, 2018). Other studies have also reported on a global inter-ictal decrease of EEG activity (Tsounis and Varfis, 1992; Cao et al, 2016) and on an association between slower alpha activity and greater disease and attack durations (Bjørk et al, 2009). Whereas in FM, decreased alpha, increased beta (Vanneste et al, 2017) and augmented theta activity (Fallon et al, 2018) have been found in different cortical areas and have also been reported to positively correlate with clinical symptoms.…”
Section: Abnormal Eeg Responses As a Shared Mechanism For Smd And Painmentioning
confidence: 91%
“…A ratio lower than 1 may be an indicator of the disturbance of neuronal excitability of the visual cortex common in migraine (1,10,12,13,15). We conclude that the ratio obtained from GFP data may provide stable parameters and reproducible results.…”
Section: Discussionmentioning
confidence: 77%
“…Further investigation will be needed to obtain comparable ratios from patient EEG data. Within this context, migraine and headache patients will be of special interest, since previous studies along with preliminary findings in our clinical experience suggest that migraine patients show significantly different electrophysiologic patterns of reaction to IPS with a flashlight in comparison to healthy controls (10,12,15). Within this context, missing suppression or even an activation of brain waves during 20-Hz IPS is to be expected in migraine patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations